TRADISI RESEPSI AL-QUR'AN DI MASYARAKAT GEMAWANG SINDUADI MLATI YOGYAKARTA: (Kajian Living Qur'an) - M.Ulil Abshor (QOF, 2019)
Islam springing of the Qur'an is understood as an ideology that gives birth to behavior in the social tradition of society. Likewise the meaning of giving birth exegesis (social interpretation). understanding and meaning of the Qur'an is called "Living Qur'an". The study of the living of the Qur'an, the author examines the tradition of the Al-Qur'an reception in the community of Gemawang Sinduadi Mlati Sleman Yogyakarta. There are 3 traditional traditions of the Al-Qur'an reception, namely the tradition of exegesis receptions, aesthetic receptions and functional receptions. The typology of the study was used to observe the Qur'anic reception tradition in Gemawang Sinduadi Mlati hamlet, Sleman, Yogyakarta. What needs to be revealed from this research is about the motivation and purpose of each Qur'anic reception which is used as the basis for understanding and interpreting daily life. This research is qualitative, in the form of library studies and field studies at the same time. The author uses phenomenological analysis and content. The results obtained there are 2, namely the outer structure surface structure indicates that the community is a society that is calm in its heart and behavior (religious behavior). While the Deep Structure element or structure in the indication is a message of close relations between fellow humans who do not see race, ethnicity, religion or ethnicity.